The Image of the Ukranian War in the Digital Media: Year 2023 - Gómez López, Jacinto; Martínez González, Paula (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Information technologies have consolidated new forms of communication: traditional media are implementing new strategies to reach audiences; audiences in turn are increasingly involved in the creation of content; and there is a growing proliferation of fake news. By using secondary sources of information through the review of academic literature and the collection of data using statistical analysis tools, the aim is to identify common patterns and differences in the image projected by the selected media on the conflict, as well as to detect fake news.